Gauging future prospects of green products in Malaysia / Mohd Rafi Yaacob - Yaacob, Mohd Rafi (2010)
Consumers are increasingly better informed and more aware of the environmental impact of products, and may demand businesses improve their environmental performances. Their pressure has often been cited in the literature as one of the important factors contributing to business environmental commitment as they may exert pressure by boycotting the products of environmentally unfriendly businesses. Due to increasing green consumerism since the early 1990s in developed countries, green products have increased significantly. Additionally, the emergence of green consumerism implies that some consumers are willing to pay a price premium. While the prospects look bright for green products in developed countries, little research has been done on the same phenomenon in developing countries including Malaysia. In contrast to developed countries, in general, developing countries’ businesses are operating in business environments that rarely reward environmentally friendly products. Customers’ low disposable incomes force them to fulfil their lower basic needs rather than demanding green products which are considered as in the higher hierarchical needs. Furthermore, consumers are often less able to make informed choices about products due to illiteracy and inadequate formal education, and a lack of necessary information about the products. However, those arguments are open to question, since the burgeoning middle class customers over several decades in developing countries has resulted in increased demand for more green products. Against the above background, the main purpose of this study is to investigate the prospects of green products in Malaysia, using 150 customers of a well-known supermarket in Kuantan, Pahang as a case. The data of the study were collected through close-ended questionnaires in March 2008. Overall, the majority of customers were not only aware of the existing green products in the market but at the same time had positive attitudes of the products. Furthermore, a majority of the respondents reacted positively to the prospects of green products in the country. Overall, results of the study show a bright future for green products in the country.